The Holocaust Museum of Curitiba from the perspective of Contemporary Museology (Master) (Cadernos de Sociomuseologia, 2016)
The present dissertation supports the hypothesis that the processes  of research, preservation and communication  of the operational museological chain involved in the conception  of long term exhibitions and program  of actions  of museums and memorials related to the theme  of Holocaust promote the realization  of the social function  of museums ln contemporary society, once they constitute a tool  of knowledge, education and mobilization in service  of the development  of critical and more socially responsible individuals and  of the diffusion  of a culture  of peace, overcoming racism, discrimination and intolerance, and human rights preservation. The dissertation presents the Holocaust Museum  of Curitiba as a case study, a cultural and educational institution dedicated to researching, preserving and communicating the memory and history  of the Holocaust. Keywords: Human Rights; Holocaust; Memory;  Musealization;  Holocaust Museum of Curitiba